Implementation of Education Quality Assurance Policy: Between Expectations and Reality - Deding Ishak (Jurnal Pendidikan Indonesia, 2023)
The main objective of the research is to analyze the extent to which the education quality assurance policy is implemented at the daily implementation level and the extent to which the expectations stated in the policy can be realized. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of education quality assurance policies in Indonesia, especially in the aspects of accreditation, student learning evaluation and teacher certification, is still faced with serious challenges. Fraudulent practices in student learning evaluations, such as leakage of exam questions, and discrepancies between formal certification and teachers' actual competence, are major concerns. Lack of commitment from policy actors and education managers is the main obstacle in achieving the desired increase in the quality of education. Therefore, concrete action is needed which is supported by a joint commitment from all parties involved to ensure continuous improvement in the quality of education in Indonesia.